التوافق النفسي الاجتماعي وعلاقته بالرضا عن الحياة لدى طلاب الجامعة - خاوة, فاطمة الزهرة; جويدة, عبابسة (University of Eloued جامعة الوادي, 2021)
الملخص: تهدف الدراسة الحالية إلى الكشف عن علاقة التوافق النفسي الاجتماعي بالرضا عن الحياة، والتعرف على دلالة الفروق بين أفراد العينة في كل من التوافق النفسي الاجتماعي والرضا عن الحياة حسب الجنس (ذكور/ إناث)، والتخصص (علوم إنسانية واجتماعية/ علوم وتكنولوجيا)، وباستخدام المنهج الوصفي الارتباطي، تم إجراء الدراسة على عينة قدرها (200) طالبا وطالبة من طلبة السنة الأولى ماستر بجامعة الشهيد حمه لخضربالوادي2021، اختيروا بطريقة طبقية عشوائية من كليتي العلوم الإنسانية والاجتماعية وكلية العلوم والتكنولوجيا، وطبقت عليهم أداتي الدراسة: استبيان التوافق النفسي الاجتماعي من إعداد بشارة كمال نقلا عن الدكتورة سهير إبراهيم (2004)، ومقياس الرضا عن الحياة من إعداد مجدي الدسوقي(1996)، وبعد التأكد من الخصائص السيكو مترية للأداتين تم إجراء الدراسة الميدانية، فكانت النتائج كالتالي: - توجد علاقة ذات دلالة إحصائية بين التوافق النفسي الاجتماعي والرضا عن الحياة لدى أفراد عينة الدراسة. - توجد فروق ذات دلالة إحصائية في درجات التوافق النفسي الاجتماعي لأفراد العينة تعزى لمتغيري الجنس والتخصص وذلك (لصالح الذكور بالنسبة لمتغير الجنس، أما بالنسبة للتخصص فكانت لصالح كلية العلوم والتكنولوجيا). - لا توجد فروق ذات دلالة إحصائية في درجات الرضا عن الحياة لأفراد العينة تعزى لمتغيري الجنس والتخصص. Abstract :انجليزية The current study aims to reveal the relationship of psychosocial compatibility with life satisfaction, and to identify the significance of the differences between the sample members in both psychosocial compatibility and life satisfaction according to gender (males / females), and specialization (human and social sciences / science and technology), and by using the curriculum. Relational descriptive, the study was conducted on a sample of (200) male and female students of the first year Master at the University of Martyr Hama Lakhdar in Wadi 2021, they were selected in a randomized stratified method from the Faculties of Humanities and Social Sciences and the College of Science and Technology, and the two study tools were applied to them: the Psychosocial Compatibility Questionnaire prepared by Bishara Kamal According to Dr. Soheir Ibrahim (2004), and the measure of satisfaction with life prepared by Magdy El Desouki (1996), and after verifying the psychometric properties of the two tools, a field study was conducted, and the results were as follows: -There is a statistically significant relationship between psychosocial compatibility and life satisfaction among the study sample. - There are statistically significant differences in the scores of the psychosocial compatibility of the sample members due to the variables of sex and specialization (in favor of males for the variable of sex, as for specialization, it was in favor of the College of Science and Technology. - There are no statistically significant differences in the degrees of life satisfaction for the sample members due to the variables of sex and specialization.
دراسة ميدانية بجامعة الشهيد حمه لخضر –الوادي-
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التوافق النفسي، الرضا عن الحياة; Adaptation psychologique, satisfaction de vivre; Psychological adjustment, life satisfaction